Antibiotic Exposure Profiles in Trials Comparing Intensity of Continuous Renal Replacement Therapy. Issue 11 (November 2019) - Jang, Soo Min; Pai, Manjunath P.; Shaw, Alexander R.; Mueller, Bruce A.
Abstract : Objectives: To determine whether the probability of target attainment over 72 hours of initial therapy with beta-lactam (cefepime, ceftazidime, piperacillin/tazobactam) and carbapenem (imipenem, meropenem) antibiotics were substantially influenced between intensive and less-intensive continuous renal replacement therapy groups in the Acute Renal Failure Trial Network trial and The RENAL Replacement Therapy Study trial. Design: The probability of target attainment was calculated using pharmacodynamic targets of percentage of time that free serum concentrations (fT): 1) were above the target organism's minimum inhibitory concentration (≥ fT > 1 × minimum inhibitory concentration); 2) were above four times the minimum inhibitory concentration (≥ % fT > 4 × minimum inhibitory concentration); and 3) were always above the minimum inhibitory concentration (≥ 100% fT > minimum inhibitory concentration) for the first 72 hours of antibiotic therapy. Demographic data and effluent rates from the Acute Renal Failure Trial Network and RENAL Replacement Therapy Study trials were used. Optimal doses were defined as the dose achieving greater than or equal to 90% probability of target attainment. Setting: Monte Carlo simulations using demographic data from Acute Renal Failure Trial Network and RENAL Replacement Therapy Study trials. Patients: Virtual critically ill patients requiring continuous renal replacement therapy. Interventions: None. Measurements and Main Results: The pharmacodynamic target of fT greater than 1 × minimum inhibitory concentration led to similarly high rates of predicted response with antibiotic doses often used in continuous renal replacement therapy. Achieving 100% fT greater than minimum inhibitory concentration is a more stringent benchmark compared with T greater than 4 × minimum inhibitory concentration with standard antibiotic dosing. The intensity of effluent flow rates (less intensive vs intensive) did not substantially influence the probability of target attainment of antibiotic dosing regimens regardless of pharmacodynamic target. Conclusions: Antibiotic pharmacodynamic target attainment rates likely were not meaningfully different in the low- and high-intensity treatment arms of the Acute Renal Failure Trial Network and RENAL Replacement Therapy Study Investigators trials.